Marketing Housing - Moschis G.P. (2023)
This chapter highlights the increasing number of older persons who prefer to age in place. The housing and remodeling industries have been responding to this trend by developing new single-family homes or converting old houses to make them suitable to the aging person’s needs. Similarly, the retirement housing industry has been responding by building facilities different from the traditional homes designed exclusively for persons of old age. The increasing diversity of the older consumer needs for housing is in part due to the gains in life expectancy that create more challenges to marketers of housing projects. Increase in life expectancy creates greater the heterogeneity of the housing market and demand for specific types of retirement and non-retirement housing. Older consumers are becoming more demanding of housing facilities and the relevant services they expect to receive from the community and other professionals. The information presented in this chapter suggests that housing for the elderly cannot be addressed in isolation from the wide variety of services the aging person needs. Rather, housing needs to be addressed in concert with other elements that are related to housing such as project financing, healthcare needs of the elderly, and social support services in the community.